(untitled) (Fiep Bulletin - online, 2011)
The study aimed investigating the relationship between school environment and risk behavior in adolescents to validate the research instrument. 48 students participated in the research of both sexes, 32 girls and 16 boys aged 17.97 + 18.19 + 1.66 and 1.47, respectively. The data collected show a prevalence of 74% of young people as normal, 18.7% as malnourished and 6.3% as overweight. Prevalence of 95.8% of the school as "sedentary" and only 4.2% were "moderately active". Observe that 89.6% of students are presented with healthy behaviors, and 10.4% with health risk behaviors. The reproducibility of the physical activity level had strong concordance rates that ranged from "perfect" and "great." Already Kappa values for the data obtained in T1 and T2 in relation to dietary habits showed a good and regular degree of agreement. The questionnaire was shown with good reproducibility, and its proper application to adolescents.